Fatigue Analysis for Shaft of Inland River Ship Under Ice Load - Kai Yang; Guoqing Feng (Journal of Marine Science and Engineering)
Inland river ships navigating in an ice area cannot avoid contact between the propeller and ice block. In addition to ensuring the safety of propeller blades, the fatigue strength of the propulsion shaft system under ice load excitation must also be considered. This paper first studies how to calculate the natural frequency of free torsional vibration of the system, then uses Newmark integral programing to calculate the maximum torsional stress of shaft system under ice load at resonance speed. Low cycle stress and high cycle stress are studied according to fatigue analysis theory. The method of determining S–N curve and ice load stress spectrum is given and the cumulative damage ratio is calculated based on Palmgren–Miner linear cumulative damage theory. Finally, taking a real inland river vessel propulsion shaft system as an example, the fatigue strength of the shaft system under different working conditions of ice load excitation is studied. Therefore, this study has practical significance and engineering application value in conducting fatigue research on the propulsion shaft system of an inland waterway vessel sailing in an ice area.